Developing English Material for Food and Beverage Service Used by Students at SMKN 1 Singaraja - Santhi, I Gusti Ayu Ira Krishna; Wedhanti, Nyoman Karina; Mahendrayana , Made (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2023)
This study aimed to determine the English for Food and Beverage Service needs of eleventh-grade students of Tourism Majors at SMKN 1 Singaraja, to design and develop the English material for Food and Beverage Services used by 11th-grade students at SMKN 1 Singaraja, to determine the quality of the developed material. This research used the Design and Developments model that Rickey and Klein (2009) suggested, which includes planning, development, and evaluation. The instruments used were interviews, questionnaires, and document analysis. The findings of this study revealed the student’s needs (necessities, wants, lacks, input, setting, procedure, the student’s role, and the teacher’s role) which are important for improving the student’s motivation and achievement in learning. Three units were developed based on the document analysis: Taking Reservations by Telephone, Receiving and Seating Guests, and Taking Food and Beverage Orders. The material is developed based on the theory proposed by Hutchinson, T., & Waters, (1987). This includes input, content focus, language focus, and task. The quality of the product’s effectiveness was evaluated by the theory proposed by Litz, (2005). After calculating data from the expert judges, the quality of the developed material can be categorized as very good material. Thus, it can be a supplementary source for learning English for Food and Beverage Service at SMKN 1 Singaraja.